Obstacle avoidance for unmanned aerial vehicles (UAV) - Chong, Charles Jin Jia (Nanyang Technological University, 2024)
In recent years, Unmanned Aerial Vehicles (UAV), otherwise known as drones have been increasingly popular due to their wide range of usage from aerial photography to military usage in combat. However, with increase in drone activities, means increase in chance of accidents such as collisions. The aim of this research is to implement a cost-efficient drone, that can perform obstacle avoidance capabilities by conducting research and simulations in hopes of getting the best cost-to-performance ratio. The model would be simulated on the software MATLAB/Simulink by varying the parameters and variables to simulate as action and reaction of the drone. The varying of these parameters and variables can be seen as adjusting the physical components used in the drones. Obstacle avoidance has been met; however, the results were not highly satisfactory especially in hitting specific waypoints and smoother controls. It is in hope that this finding would be a step closer to making obstacle avoidance in aerial robots affordable.